MEANINGS OF WORK: RESEARCH ITINERARIES IN A SYSTEMATIC LITERATURE REVIEW (Management and Connections Journal, 2024)
The studies on the meanings of work stem from a longstanding tradition, and despite the increasing interest in the subject, there exists a gap in the literature concerning systematic review studies. Therefore, this article provides a comprehensive review, examining the social and intellectual structure of research, identifying the boundaries of knowledge in academic production related to the meanings of work, and proposing an agenda for conducting new studies. Beyond the quantitative aspects of publications, citations, major journals, and research areas, the findings indicate that meanings can be explored within three domains: personal, professional, and social. There are research propositions suggested by seminal authors that, as of now, appear unexplored, presenting new avenues for research. Some studies exhibit conceptual inaccuracies in analyzing the phenomenon. The absence of epistemological coherence, noted in certain cases, emerges as the most critical point identified in this review.
Keywords: Meanings of work; Systematic review; Meaningful work